The first book of Microsoft Word 5 - Heslop, Brent D. 4 0 16; Angell, David; 5 (Carmel, IN, USA : H.W. Sams, 1990)
Instructions for creating, editing and printing documents, formatting, managing document files, using windows, and spell checking for the word processing program.
Includes index.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Microsoft Word; Computer programs. -- Word processing;Microsoft Word (Computer program);Word processing; 20; 2